EDITORIAL NOTE Vol. 64 (12/2025) RA’E GA – THE GEOGRAPHIC SPACE UNDER ANALYSI - Breunig, Fábio Marcelo; Almeida, Catherine Torres de; Sordi, Michael Vinicius de (Ra’e Ga: o Espaço Geográfico em Análise, 2025)
RA’E GA – THE GEOGRAPHIC SPACE UNDER ANALYSIS is pleased to present to the national and international scientific community the 3rd volume of 2025 (V.64 – 12/2025 - DOI: http://dx.doi.org/ 10.5380/raega.v64i1.101109). This volume contains articles covering various topics related to Geographic knowledge and other scientific domains. The journal continues to be published in both English and Portuguese. This strategy aims to preserve the structure of the texts and increase accessibility for readers worldwide. According to initial results from the Dimensions platform, the average citation index per article increased to 1.41 between 2024 and 2025. Over the past decade (2014–2024), citations on the platform increased from approximately ten to over two hundred. This demonstrates the community’s recognition of the manuscripts’ quality. In this edition, we introduce a new editorial process with three editors-in-chief for RA’E GA: The Geographical Space Under Analysis. We would like to thank Prof. Dr. Catherine Torres de Almeira and Prof. Dr. Michael Vinicius de Sordi for joining the team. This new structure will allow us to work more efficiently, explore new indexing opportunities, and generate new prospects for authors, ultimately benefiting both them and the journal’s audience. RA’E GA thanks the authors, editorial team, section editors, and, especially, the reviewers who worked on this volume, as well as the UFPR Periodical Scientific Publications Support Programme. This entire ecosystem is fundamental to the development of Brazilian science and was essential to the quality of this volume.